Blue Moon haven [large type] - Dailey, Janet (Dailey, Janet. New Americana series, 2023)
"Kelly Jenkins heads to bucolic Blue Moon, Alabama, believing a new life will heal the two orphaned children in her care. Signing on to revive the drive-in theater seems like a worthy venture, until she discovers the property is in deep disrepair. Still, Kelly takes on the renovation, beginning with an ancient tree that needs to come down. Seth Morgan reluctantly steps in to help Kelly, even offering her and her kids shelter in his home. Soon everyone is bound up in the fate of Blue Moon's drive-in and the new family in town. Because it looks like the love blooming between Kelly and Seth just may rival any found on the silver screen"--